Wrong Site Surgery as a Tort An Analysis of the Liability of Surgeons and Hospitals - Ghani Ikhsan Majid; Asep Sapsudin (PALAR | PAKUAN LAW REVIEW, 2026)
Wrong Site Surgery (WSS) is one of the most serious never events in health care because it is conceptually preventable, yet when it occurs it causes physical, psychological, social, and economic harm to patients. This study examines the juridical parameters of WSS as a tort and analyzes the allocation of liability between the surgeon as an individual actor and the hospital as a corporate health-care provider. The study applies a normative-analytical legal design using statutory, conceptual, and case approaches. The research target is not a statistical population but legal norms, doctrines, scientific studies, and concrete cases relevant to WSS. Data were collected through a systematic library study of primary, secondary, and tertiary legal materials. The data were analyzed qualitatively and prescriptively through grammatical, systematic, and teleological interpretation to assess the elements of tort, the surgeon’s position, and the hospital’s legal obligations. The findings show that WSS fulfills the elements of an unlawful act because it involves unlawful conduct, fault, damage, and a clear causal relationship. Surgeons bear personal liability for professional negligence in patient verification, site marking, and compliance with the time-out process, whereas hospitals may be liable under vicarious liability and corporate liability when systemic failures, weak supervision, deficient policies, and poor safety culture contribute to the event. Practically, the study underscores the importance of documented preoperative verification, audits of time-out compliance, non-punitive incident reporting, and prompt, accountable compensation mechanisms   Keywords: wrong site surgery; tort; medical liability; hospital liability; patient safety.